Zachód jako punkt odniesienia rosyjskiej polityki zagranicznej - Nadskakuła, Olga (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
The West has been one of the most significant reference criteria for the Russian political, historical or ideological thought. The reason for this is that Russian identity has been shaped mainly by virtue of comparison to the West. Therefore, Russian self-reflection is always assessed by means of Russian relation to the West. This relation has assumed various dimensions in different times, yet it has always ranged from utter admiration for the Western civilization to extreme disapproval of its achievements. At present Russia no longer develops her relations with theWest on the fragile foundations of ideology that has been substituted by the factors of national interest or higher necessity. Therefore it seems that when asked „Where are you heading, Russia?” she is going to keep answering „Westwards” for a long time to come.